Performance analysis of PV powered multilevel inverter - K. Dhineshkumar; C. Subramani; A. Geetha; C. Vimala (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This article deals with the PV based DC/DC boost chopper integrated nine level inverter. This topology requires 7 switches in minimum to obtain a nine level stepped wave output. So the main objective of this paper is to develop a 9 level AC output using PV based DC/DC boost chopper. In the case of conventional multi-level inverter, 16 switches were utilized and the number of sources needed was also more. Here the proposed system comprises of single PV panel and the switches used are also less. Also PV is integrated with DC/DC boost chopper is used to increase the source input level of the inverter. Using MATLAB platform, the proposed system is simulated with a resistive and inductive load. The similar results are obtained in prototype which validates the designed converter.